IMPLEMENTASI KURIKULUM MERDEKA PADA PELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Fatimah, Nur; Ratnasari Dyah Utami (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The Merdeka Curriculum emphasizes the active involvement of students in the learning process to provide direct experience and encourage knowledge exploration. Indonesian language subjects are the basis for learning because they focus on literacy development. This research analyzes: 1) the implementation of the Merdeka Curriculum in class III students at SD Negeri Pandean 2. 2) Effectiveness, challenges and impact on learning outcomes. With the qualitative descriptive method, data is collected through observation, interviews and documentation, then its validity is tested using triangulation of techniques and sources. Data analysis was carried out using the Miles and Huberman interactive model, including data reduction, data presentation, and drawing verified conclusions. The results: 1), Implementation of the Independent Curriculum in class III Indonesian language subjects at SD Negeri Pandean 2 succeeded in creating more active and student-centered learning. 2), Its effectiveness can be seen from increasing literacy skills and student activity, while several challenges arise, such as low interest in reading at home, limited resources, and differences in students' ability to understand the material. This curriculum increases student engagement and interest in literacy through interactive learning methods, although challenges such as low interest in reading at home and variations in student abilities remain. Government support in the form of teacher training and effective literacy programs helps overcome these challenges, although collaboration with parents needs to be improved for more optimal results.